Doctor – patient communication: What Malaysia needs - Ariffin, Adlina; Mat Zain, Nora; Abdul Manaf, Aini Maznina; Mahmud, Murni (2019)
Doctor-patient communication is a crucial, unique yet complex relationship in clinical practice due to its therapeutic qualities. With the current emphasis on patient-centred care and patient autonomy, medical practitioners are not only expected to possess clinical and biomedical knowledge but also the skills to develop a therapeutic doctor-patient relationship (Ha & Longnecker, 2010). Nevertheless, this expectation proves to be an uphill battle to physicians as evidenced from patient complaints which among others include lack of appropriate non-verbal behaviours, absence of paralinguistic elements, lack of trust and empathy (Kee, 2018). Moreover, unsatisfactory doctor-patient communication has been identified as one of the major elements in litigation cases in the medical field (Elango, 2003; Steven Chow in Chin, 2013; B-Lynch et al. (1997) in Lum, n.d). Among the fundamental factors which lead to this predicament is the ineffective training of communication skills at the medical schools (Franco et al.,2018; Jillian, 2017; Kee, 2018; Loureiro, 2017). Upon realising the gravity of the issue, this project aspires to develop a training model on doctor-patient communication skills based on patient-centred approach. The model will give more emphasis on the linguistics and psychosocial aspects of communication. Method: Utilising both qualitative and quantitative approaches, the project aims to identify 1) the key communicative features and 2) the key clinical and psychosocial features to be incorporated in the model. It will then operationalise these features to conceptualise an expert assistance system which shall be used in the training of future physicians. Conclusion: The findings from this research are significant in improvising and enhancing the current training on communication skills provided at the medical schools. With a more ‘humane’ approach to training, indirectly, it will increase the effectiveness in the delivery of health care and achieve sustainability in good health and well-being (SDG3) of the nation.